Population dynamics of Brachionus calyciflorus and Brachionus havanaensis (Rotifera) on mixed diets with Microcystis aeruginosa and green algae - Alva-Martínez, A. F.; Sarma, S.S.S.; Nandini, S. (HIDROBIOLÓGICA, 2017)
The effect of the cyanobacterium Microcystis aeruginosa was evaluated as a diet, separately and together with one of the two edible algal species (Chlorella vulgaris or Scenedesmus acutus) at different proportions (0, 25, 50, 75 or 100% on the basis of biomass) on the population growth of two rotifers Brachionus calyciflorus and Brachionus havanaensis. Population growth curves of B. calyciflorus and B. havanaensis cultured on M. aeruginosa alone, or in combination with one of the two algal species decreased with increasing proportion of cyanobacteria in the diet. In treatments containing exclusive algal diets (either Chlorella or Scenedesmus) and those with low proportion of Microcystis, B. havanaensis was more abundant than B. calyciflorus. However, both rotifer species died in less than two weeks on an exclusive diet of M. aeruginosa. Peak population densities (mean ± standard error) of B. calyciflorus grown on an exclusive diet of Chlorella or Scenedesmus were 47 ± 6 and 15 ± 1 ind. ml-1, respectively. Corresponding values for B. havanaensis were much higher (203 ± 21 and 187 ± 2 ind. ml-1). Regardless of the rotifer species and the diet type and composition, the population growth rates (r) were inversely related to increasing proportion of M. aeruginosa in the diet.